Luis G. Lumbreras, Peter Kaulicke, Julián I. Santillana y Waldemar Espinoza. Economía Prehispánica, Tomo I. Banco Central de Reserva del Perú, IEP Instituto de Estudios Peruanos, Lima, 2008, 448 pp. - Bonavia Berber, Duccio (Revista Histórica, 2025)
Sin resumen.